Assessing the Impact of Multilane Free Flow on Vehicle Operating Costs and Logistics Efficiency in Indonesia Using SWOT Analysis Approach - Hally Hanafiah; Ratna Palupi; Aisyah Syifa Ghaniyyah; Gravila Rafa Nugraha; Muhammad Emyr Ilham (Jurnal Manajemen Industri dan Logistik, 2026)
Indonesia’s logistics sector faces high costs and inefficiencies due to toll road congestion and delays. Multilane Free Flow (MLFF) offers a solution by enabling seamless toll transactions that can reduce delays and costs. Using a SWOT framework, with RBV and Institutional Theory, this study assesses MLFF’s impact. It highlights MLFF’s strengths in efficiency, lower VOC, safety, and environmental benefits. Challenges include technological accuracy, financial viability, user acceptance, and fragmented regulations. Public support offers opportunities for adoption, but implementation needs regulatory reform, infrastructure upgrades, and stakeholder collaboration. MLFF could reduce logistics costs and enhance competitiveness, but success depends on overcoming hurdles through coordinated efforts.